Prescription pattern, glycemic control status, and predictors of poor glycemic control among diabetic patients with comorbid chronic kidney disease in Ethiopia: a facility-based cross-sectional study - Oumer Sada Muhammed; Minimize Hassen; Samuel Mamusha (BMC Endocrine Disorders)
Abstract Background Achieving optimal glycemic control is vital for managing diabetes mellitus and preventing its complications, yet it is particularly challenging for individuals with diabetes and concurrent chronic kidney disease. Chronic kidney disease disrupts glucose metabolism and excretion, leading to pronounced and variable blood glucose fluctuations, thereby complicating diabetes management. So far, the intricate impact of chronic kidney disease on the glycemic control status of diabetic patients remains obscure, especially in Sub-Saharan Africa where both diseases pose an escalating burden. Objective This study aimed to assess prescription patterns, glycemic control status, and the contributing factors to poor glycemic control among diabetic patients with comorbid chronic kidney disease at Tikur Anbessa Specialized Hospital, Ethiopia. Methods A facility-based cross-sectional study was conducted from March 15 to May 15, 2024, from the electronic medical records of diabetic patients with comorbid chronic kidney disease who had received regular treatment and follow-up at the adult diabetes mellitus clinic of Tikur Anbessa Specialized Hospital. The sample size was calculated by using a single population proportion formula and accordingly, a total of 384 patients were recruited randomly and enrolled in this study. Descriptive statistics was employed for analyzing quantitative variables. Logistic regression analysis was performed to identify predictors of poor glycemic control status. Statistical significance was established at p-value < 0.05. Results This study found that 98.2% of patients had type 2 diabetes, with a mean diabetes duration of 16.36 years. Only 4.4% achieved good glycemic control (glycated hemoglobin [HbA1c] < 7%), while 95.6% had poor glycemic control (HbA1c ≥ 7%). Insulin, metformin, and sodium glucose cotransporter-2 (SGLT-2) inhibitors were the most frequently prescribed anti-diabetic drug classes which accounted for 80.2%, 59.1%, and 41.4%, respectively. Presence of hypertension (AOR: 3.70, 95% CI: 1.08–12.71, P = 0.038) and regimen change in the past 01year (AOR: 0.34, 95% CI: 0.11–1.01, P = 0.050) were predictors of poor glycemic control status. Conclusion This study reveals significant challenges in glycemic control among diabetic patients with comorbid chronic kidney disease (CKD). With only 4.4% of participants achieving optimal HbA1c levels, the findings underscore a critical public health concern regarding the management of diabetes in this vulnerable population. Clinical trial number Not applicable.